Writing Names in Music Books. Case Studies from the Viadrina Collection Held in the Music Department at University of Warsaw Library - Antonio Chemotti (Muzyka)
The Music Department at University of Warsaw Library houses a corpus of musical sources originating from the library of Viadrina University in Frankfurt an der Oder, predominantly comprising musical prints from the late sixteenth to early seventeenth century. The present article offers an overview and inventory of this corpus. Furthermore, it delves into four case studies, examining sources with annotations containing personal names. These annotations provide insights into the social context surrounding these sources, contributing both to the study of the musical culture of early modern Central European universities, and to the investigation of annotations in music books.